Interfacial Microstructure and Bonding Area of Sn-based Alloy-GG25 Gray Iron Bimetallic Material Using Flux, Sn, and Sn-Zn Interlayer Compound Casting - Fathy, N. (Engineering, Technology & Applied Science Research, 2022)
A bimetallic casting consisting of GG25 gray iron substrate and Sn-based alloy using the liquid-solid technique has been studied in this paper. Three different pretreatment processes of gray iron surface substrates including flux only, flux and Sn powder, and flux and Sn-8.8% Zn powder eutectic alloy surface treatment were adopted for the aim of improving the quality of tinning, the interfacial structure, and the bonding area of the Sn-based alloy/gray iron bimetallic composite in order to promote the bonding quality of bimetallic castings. Microstructure characterization on the bonding interface was conducted. The novel tinning material for gray cast iron substrate comprising of Sn-8.8% Zn eutectic alloy powder in combination with flux interlayer improved the bonding area, the interfacial bimetal structure, and the shear stress. This improvement is due to the higher interface reaction of Zn with Fe that leads to the formation of a very thin layer of Fe-Zn and Fe-Sn intermetallic phases.